EKSEKUSI BARANG BUKTI PADA PERKARA ILLEGAL LOGGING DI PENGADILAN NEGERI SEMARANG - Hani Irham Dessetya, Pujiyono ,Bambang Dwi Baskoro (Diponegoro Law Journal, 2012)
One of the problems in the environmental field in the forestry sector is the problem of illegal logging or known by the term "illegal logging". Crimes encourage illegal logging forestry deforestation, law enforcement has been unable to provide a deterrent effect to the perpetrators. Attorney as an implementing agency in the execution of the verdict in kracht van gewijide will run the verdict was legally binding if the decision has received a copy of a letter from the registrar (Section 270 Criminal Procedure Code). Legal writing is to discuss the security deposit and proceeds of crime evidence of illegal logging in Semarang District Court as well as the mechanisms for the execution of case evidence of illegal logging in Semarang District Court. This thesis uses the normative research methods. Specifications research is descriptive analysis. Writing this paper uses data collection techniques to study the documents and literature searches. Data and analysis is qualitative. The data was then analyzed by the approaches defined descriptively and presented in a descriptive analytical overview of the general description of the problem. Storage and security of evidence illegal logging results in Semarang District Court can be distinguished as authorized in the storage and safeguarding of evidence illegal logging results are RUPBASAN (Rumah Penyimpanan Benda Sitaan Negara) are set out in presence of the State Foreclosure Home Storage Objects ( RUPBASAN), which is regulated in Law No. 8 of 1981 on Criminal Procedure, Government Regulation. 27 Year 1983 on the Implementation of the Code of Criminal Procedure, and the Minister of Justice M.05.UM.01.06 No. 1983 on Management of Confiscated Objects and Items Confiscated by the State in the State Foreclosure Home Storage Objects. Meanwhile, those responsible for the items confiscated in the investigation and inspection is the prosecutor's office and the police department, the proceeds of crime evidence eventually placed in RUPBASAN. Storage of confiscated items should be implemented as well as possible and responsibility by the prosecutor and the thing is prohibited for use by anyone